Improving Land Sector Governance in Vietnam - Vo, Dang Hung; Thang, Nguyen Van (World Bank, Washington, DC, 2017)
The Land Governance Assessment Framework (LGAF) was designed to address these challenges by the World Bank, based on a comprehensive review of available conceptual and empirical materials regarding experience in land governance. The objective of LGAF is was developed as a diagnostic tool for a systematic evaluating and benchmarking legal framework, policies and practices regarding land and land use. This document represents the country report for Vietnam’s national LGAF Study. This important exercise was undertaken by team of national experts, with support from the World Bank, and in collaboration with the Ministry of Natural Resources and Environment (MoNRE) in 2013. The Study’s objective was to provide the means for better understanding the strengths and weaknesses of the Vietnamese land sector; establish a consensus on the status of land governance in the country and identify priority actions for regulatory and institutional changes and the piloting of new approaches to improve land governance on a broader scale.The Study’s Report describes the process for LGAF implementation and the country context. The assessment of land governance is also presented, as well as the policy analysis, conclusions and recommendations. The report is intended to serve as a reference guide for policy makers and land practitioners in the government and non-government organizations such as private sector, academe and other groups to help shape the direction, focus and support for the land sector, and how progress in improving governance can be effectively monitored.